2013
DOI: 10.1136/tobaccocontrol-2012-050888
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost of a smoking employee

Abstract: Employees who smoke impose significant excess costs on private employers. The results of this study may help inform employer decisions about tobacco-related policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 32 publications
3
128
1
Order By: Relevance
“…Smoking also causes significant societal consequences globally in the form of work productivity impairment. Working smokers in the US are estimated to miss an average of 2.3 more workdays annually than those who have never smoked and be less productive while at work 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Smoking also causes significant societal consequences globally in the form of work productivity impairment. Working smokers in the US are estimated to miss an average of 2.3 more workdays annually than those who have never smoked and be less productive while at work 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…2015 25 showed that although effectiveness was halved 6 months after stopping incentives, it was still good (RR= 2.17). As the estimated annual excess costs of employing a smoker can range around US$5816 (€4482, GDP‐based PPP‐ and inflation‐adjusted, currency year 2015) 45, smoking‐related costs are likely to be higher than financial incentive programme costs, even on an annual basis 25. Another risk of financial incentive programmes is the enrolment of non‐smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, not only are nonsmoking workers generally healthier, but they are more productive and less costly for employers. Considering aggregate cost and productivity impacts, one recent study estimated that the annual cost to employ a smoker was, on average, nearly $6,000 greater than the cost to employ a nonsmoker [Berman et al 2013]. It follows that interventions that help smoking workers quit can benefit the bottom line of a business.…”
Section: Preventive Interventionsmentioning
confidence: 99%
“…Considering aggregate cost and productivity impacts associated with smoking breaks, absenteeism, presenteeism, healthcare expenses, and pension benefits, the study estimated that the annual cost to employ a smoker was, on average, $5,816 greater than the cost to employ a nonsmoker [Berman et al 2013]. Interventions that help smoking workers quit can benefit a business' bottom line [NBGH 2013].…”
Section: Niosh Cib 67 • Workplace Tobacco Policiesmentioning
confidence: 99%